Impact on Stock Market Performance for the Companies that Contributed to the Chandrayaan-3 Project - Kowsalya, P.; Valarmathi, A.; Akshaya, D. (Indian Journal of Research in Capital Markets, 2024)
Purpose : The study focused on the performances and investment opportunities of the companies that contributed to the Chandrayaan 3 Project. Methodology : The study was conducted for the 10 companies that contributed to Chandrayaan 3. The six months’ stock prices from February 2023 to August 2023 were taken for the study. The research design was descriptive. We analyzed the data using tools like Tobin’s Q ratios, moving averages, RSI, MACD, candlestick charts, and parabolic SAR. Findings : The study showed the investment opportunities in the 10 companies, the future forecast, and the growth level of the stock prices. Tobin’s Q ratio results in the overvaluation or undervaluation of a company’s physical assets, which helps to identify the buy and sell strategies of these companies’ assets. Practical Implications : The study suggested that the technical tools help the investors to identify better investment opportunities in the company’s equity based on the market risk exposure. Originality : The study was performed to know how far the launch of Chandrayaan 3 has implications on the stock price movements of the companies that contributed to the Chandrayaan 3 Project.